LdoD Archive: User Experience and Identity Design Processes - Santos, Tiago José Miranda (2015)
LdoD Archive is a dynamic web archive dedicated to Fernando Pessoa’s Book of Disquiet. It is an archive built on HTML, Javascript and TEI technology, among others, which allows users to generate not only comparative readings across the editions, but also a genetic view of Fernando Pessoa’s writing processes. In this paper we will address the user experience and identity design processes implemented. Our analysis is based on structured and semi-structured interviews and tests on the uses of the application. (1) (PDF) LdoD Archive: User Experience and Identity Design Processes. Available from: https://www.researchgate.net/publication/280621302_LdoD_Archive_User_Experience_and_Identity_Design_Processes [accessed Jun 17 2020].